EMPOWERMENT OF ELDERLY POSYANDU VOLUNTERS IN EARLY DETECTION OF HYPERTENSION DISEASE - Hariyono, Hariyono; Sri Pantja Madyawati; Syifa Fauziyah; Candra Panji Asmoro; Teguh Hari Sucipto; Leo Yosdimyati Romli; Risanti Handayani (Frontiers in Community Service and Empowerment, 2023)
The number of elderly populations in various countries continues to increase along with increasing life expectancy, so it is important to pay special attention to the health of the elderly, including early detection of hypertension. Posyandu volunters have good access to the elderly population because they are actively involved in community health activities. The aim of empowering elderly Posyandu volunters is to increase volunters' knowledge and skills in early detection of hypertension in the elderly. With adequate knowledge, volunters can provide better care and prevent more severe complications. The results of this research were that more than half had poor knowledge about early detection of hypertension before being given training (56%) and most of them had good knowledge about early detection of hypertension after being given training (63%). Empowering elderly Posyandu volunters has significant benefits. Skilled volunters can help increase elderly awareness of the importance of early detection of hypertension. Apart from that, volunters can provide assistance in regular health monitoring so that elderly people can take preventive measures in a timely manner..